UI/UX Design of a Production Information System at PT Belitang Panen Raya Using the Design Thinking Method - Faizi, Nur; Purwaningtias, Fitri; oktarina, Tri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The people of Asia, especially Indonesia, have a staple food, namely rice. Rice is a major and strategic food commodity whose availability needs to be guaranteed. To provide the best in inputting incoming and outgoing goods data as well as available goods data, Belitang Harvest Raya designed a new application product. In this study using the Design thinking approach. The Design thinking method is an innovation-based software product design method that is based on finding solutions to solve certain problems. After successfully finding and understanding the problems obtained through the process of Identify the problem, Describe Solution, Empathize to Users, Appeal to Business, Lock in Agreement (IDEAL) and Prototype and Test. So that the BPR application is able to solve problems that occur in a company at this time.